The effect of organizational differentiation in football training on young football players - Størdal, Olav; Dalen, Terje; Lagestad, Pål (Frontiers in Psychology, 2025)
IntroductionThe Norwegian Football Federation (NFF) has a primary goal of providing children and adolescents with a good football offer and positive football experiences, where differentiation is one way to achieve this. The aim of the present study was to investigate the effect organizational differentiation has on psychological and physical variables in 13–14-year-old male football players.MethodsAn intervention study with an experimental randomized crossover design was used, where players from three football teams participated in two differentiated training sessions and two non-differentiated training sessions. The four training sessions had the same exercises, with the same coach. The physical measurements involved heart rate, number of accelerations, number of sprints and total distance covered measured by Polar Team Pro GPS, while the psychological variables measured in a questionnaire was wellbeing, mastery, joy, satisfaction and experienced development. Wilcoxon nonparametric tests were used to compare the results from differentiated and non-differentiated sessions.ResultsThe results showed that players with upper-level skills (UG) experienced significantly higher enjoyment, satisfaction, and development in differentiated training compared to non-differentiated training and preferred differentiated training. No significant differences were observed in psychological variables between differentiated and non-differentiated training among lower-group players. Furthermore, all players had more accelerations and increased their total distance covered during differentiated training compared to non-differentiated training regardless of group. Finally, players in UG had a higher average heart rate during the entire session, as well as in the sub-exercises SSG, 2v2+1 games, and rondo 4v1.DiscussionThe results suggest that organizational differentiation positively affects young players' physical variables, especially players with upper-level skills. Organizational differentiation also positively affects psychological variables of young players with upper-level skills. However, careful consideration should be given to the potential long-term consequences of differentiation for lower-skilled players, especially regarding social belonging and self-perception.